2013
DOI: 10.1021/bm400993f
|View full text |Cite
|
Sign up to set email alerts
|

Cation-Induced Hydrogels of Cellulose Nanofibrils with Tunable Moduli

Abstract: Cellulose nanofibrils are biocompatible nanomaterials derived from sustainable natural sources. We report hydrogelation of carboxylated cellulose nanofibrils with divalent or trivalent cations (Ca(2+), Zn(2+), Cu(2+), Al(3+), and Fe(3+)) and subsequent formation of interconnected porous nanofibril networks. The gels were investigated by dynamic viscoelastic measurements. The storage moduli of the gels are strongly related to valency of the metal cations and their binding strength with carboxylate groups on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
301
3
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 339 publications
(321 citation statements)
references
References 31 publications
12
301
3
5
Order By: Relevance
“…Gel strength can be improved by e.g. gelation with di-or trivalent cations, such as Ca 2+ , 27 whereas TEMPO CNF lm wet strength can be enhanced by interbrillar bridging using e.g. polyvinyl alcohol, PVA 28 or by photocrosslinking.…”
Section: -26mentioning
confidence: 99%
See 1 more Smart Citation
“…Gel strength can be improved by e.g. gelation with di-or trivalent cations, such as Ca 2+ , 27 whereas TEMPO CNF lm wet strength can be enhanced by interbrillar bridging using e.g. polyvinyl alcohol, PVA 28 or by photocrosslinking.…”
Section: -26mentioning
confidence: 99%
“…The cations draw adjacent brils together, which prevents water molecules from solvating their surface, increasing their mechanical stability in water. 27 Hence, in order to create hydrogel layers with increased performance in a submerged state, the layers with entrapped C. reinhardtii cells were stabilized by Ca 2+ and placed in sulfate/phosphate-free medium in the vials under an Ar atmosphere. Here, algae entrapped in CNF hydrogels yielded more H 2 than the cells entrapped in alginate (Fig.…”
mentioning
confidence: 99%
“…3 The defibrillation efficiency can be further aided by mild to moderate mechanical post-treatments that have included magnetic stirring, 4 ) cations could cause hydrogelation via chelation with CNF carboxylate anions 8,9 and protonation of sodium carboxylate to carboxylic acids could induce gelation to pH-responsive CNF hydrogels.…”
Section: ■ Introductionmentioning
confidence: 99%
“…3 The defibrillation efficiency can be further aided by mild to moderate mechanical post-treatments that have included magnetic stirring, 4 blending, 1,5 and brief sonication 6,7 to produce CNFs with varied surface carboxyls/carboxylates and geometries. ) cations could cause hydrogelation via chelation with CNF carboxylate anions 8,9 and protonation of sodium carboxylate to carboxylic acids could induce gelation to pH-responsive CNF hydrogels. 10−12 Fully protonated CNFs also have shown to exhibit much better dispersibility in polar aprotic solvents, such as N,N-dimethylacetamide (DMAc), dimethyl sulfoxide (DMSO), N,N-dimethylformamide (DMF), 1,3-dimethyl-2-imidazolidinone (DMI), and 1-methyl-2-pyrrolidone (NMP).…”
Section: ■ Introductionmentioning
confidence: 99%
“…Previous work has shown that aqueous dispersions of slender and kinked CNFs display non-Newtonian rheological behavior characterized by shear thinning and pronounced viscoelastic behavior at concentrations above the gelation threshold (de Kort et al 2016;Jowkarderis and van de Ven 2015;Martoia et al 2016). Recent studies have investigated the effects of pulp source (Tanaka et al 2016), fibril dimension and concentration (Agoda-Tandjawa et al 2010), mechanical treatments (Pääkkö et al 2007), ionic strength (Dong et al 2013), pH (Fall et al 2013), as well as addition of amphiphilic molecules (Quennouz et al 2016) on the rheology of CNF dispersions. Additionally, CNFs can also assist in preparation of homogeneous dispersions of a variety of fillers and pigments, such as carbon nanotubes (Hamedi et al 2014), reduced graphene oxide (Duan et al 2016), TiO 2 (Schütz et al 2012), and CaCO 3 (Lourenço et al 2016) nanoparticles.…”
Section: Introductionmentioning
confidence: 99%